FUZZY PRODUCTION MODEL OF URBAN PUBLIC PASSENGER TRANSPORT SUSTAINABLE DEVELOPMENT - Vdovychenko, V.; Вдовиченко, В. А.; Вдовиченко, В. О. (Харьковский национальный автомобильно-дорожный университет, 2017)
The structure of unclear production model of steady development of urban public passenger transport, which is based on the selection of risk factors, estimation of the character of its multilevel connections within the limits of a single transport space, has been worked out. The fuzzy production rules of forming the risks of constancy are presented from the perspective of influence on the municipal environment.
НЕЧЕТКАЯ ПРОДУКЦИОННАЯ МОДЕЛЬ УСТОЙЧИВОГО РАЗВИТИЯ ГО-РОДСКОГО ОБЩЕСТВЕННОГО ПАССАЖИРСКОГО ТРАНСПОРТА
НЕЧІТКА ПРОДУКЦІЙНА МОДЕЛЬ СТАЛОГО РОЗВИТКУ МІСЬКОГО ГРО-МАДСЬКОГО ПАСАЖИРСЬКОГО ТРАНСПОРТУ
Keywords: public passenger transport; risk; steady development; городской пассажирский транспорт; риск; устойчивое развитие; міський пасажирський транспорт; ризик; сталий розвиток; 656.025.2